Mental Health Consequences of the Coronavirus 2020 Pandemic (COVID-19) in Spain. A Longitudinal Study - González-Sanguino, Clara; Ausín, Berta; Castellanos, Miguel Ángel; Saiz, Jesús; López-Gómez, Aída; Ugidos, Carolina; Muñoz, Manuel (Frontiers in Psychiatry, 2020)
Background: Covid-19 remains a pandemic that most countries in the world are still dealing with. This is the first study in the scientific literature to report the psychological impact of Covid-19 over time on the Spanish population. Methods: A longitudinal study (N = 1041) was carried out with two measurements: after two and five weeks starting from the declaration of the state of emergency in Spain. The presence of depressive symptoms, anxiety and posttraumatic stress disease (PTSD) was evaluated by means of screening tests. Sociodemographic data, variables about Covid-19, loneliness, psychological well-being, social support, discrimination and a sense of belonging were collected. Results: The data showed how depressive symptomatology increased significantly over time, while anxiety and PTSD did not show statistically significant changes. Psychological well-being and loneliness were the main predictors of psychological impact. A younger age was a significant predictor of depression and anxiety, while female gender was associated with anxiety and PTSD. Conclusions: The impact of the pandemic is sustained over time, even increasing in depression, and vulnerable groups that need greater psychological health support could be identified.